Uveitis in patients with axial spondyloarthritis or psoriatic arthritis: a post hoc analysis from placebo-controlled phase III studies with secukinumab - Jan Brandt-Jürgens; Martin Rudwaleit; Frank Behrens; Christopher Ritchlin; Daniel Peterlik; Erhard Quebe-Fehling; Atul Deodhar (Therapeutic Advances in Musculoskeletal Disease)
Background: The incidence rate of uveitis in secukinumab-treated patients with axial spondyloarthritis (axSpA) was previously reported. Objective: To evaluate the incidence rate of uveitis in patients with axSpA and psoriatic arthritis (PsA) treated with secukinumab or placebo during placebo-controlled phase III studies. Design: This was a post hoc analysis from 11 phase III studies. Methods: Pooled data from axSpA (MEASURE 1–5 and PREVENT studies) and PsA (FUTURE 1–5 studies) were analyzed. Results: In the axSpA cohort ( N  = 1980), the incidence rate for uveitis was 1.29 per 100 patient-years in the secukinumab 150 mg and 1.72 per 100 patient-years in the placebo arm. In the PsA cohort ( N  = 2453), the incidence rate for uveitis was 0.71 per 100 patient-years in the secukinumab 300 mg arm; no events were reported in the placebo arm. Conclusion: During the placebo-controlled phase, a numerically lower incidence of uveitis was observed in secukinumab-treated axSpA patients. In PsA patients, the incidence was low in secukinumab-treated patients, while uveitis was not reported in the placebo group.